2023
DOI: 10.1002/ange.202215933
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Harvesting of Multiple Hot Holes via Visible‐Light Excitation of Plasmonic Gold Nanospheres for Selective Oxidative Bond Scission of Olefins to Carbonyls

Abstract: Using visible photoexcitation of gold nanospheres we successfully demonstrate the simultaneous harvesting of plasmon-induced multiple hot holes in the complete oxidative scission of the C=C bond in styrene at room temperature to selectively form benzaldehyde and formaldehyde, which is a reaction that requires activation of multiple substrates. Our results reveal that, while extraction of hot holes becomes efficient for interband excitation, harvesting of multiple hot holes from the excited Au nanospheres becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…A recent study revealed that multiple hot holes contribute to alkene oxidation through two consecutive elementary steps: the binding of molecules to the Au surface and the formation of a cyclic oxometallate species (Figure 4a). 50 Our recent real-space study demonstrated that multiple reaction pathways: hopping, rotation, and dissociation, are available with hot-carrier transfer, based on a single-molecule study of oxygen molecules (Figure 4b). 53 More complicated catalytic reactions would be achieved with the involvement of multiple hot carriers and multiple reaction pathways.…”
Section: ■ Diverse Excitation Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that multiple hot holes contribute to alkene oxidation through two consecutive elementary steps: the binding of molecules to the Au surface and the formation of a cyclic oxometallate species (Figure 4a). 50 Our recent real-space study demonstrated that multiple reaction pathways: hopping, rotation, and dissociation, are available with hot-carrier transfer, based on a single-molecule study of oxygen molecules (Figure 4b). 53 More complicated catalytic reactions would be achieved with the involvement of multiple hot carriers and multiple reaction pathways.…”
Section: ■ Diverse Excitation Sourcesmentioning
confidence: 99%
“…43 In recent years, the generation and utilization of hot holes for chemical reactions have also attracted increasing attention. 44−47 Recent studies have revealed that hot holes can enhance or induce various chemical reactions such as the oxidative dissolution of Au nanorods, 48 azo coupling reaction of adenine, 49 and oxidative scission of the C�C bond, 50 and so on.…”
Section: ■ Diverse Excitation Sourcesmentioning
confidence: 99%